THE EFFECT OF TRADITIONAL GAMES GOBAG SODOR AND BENTENGAN ON THE LOCOMOTOR FUNDAMENTAL MOVEMENT SKILLS OF ELEMENTARY SCHOOL STUDENTS - Bela Kiara Ananta; Sayuti Syahara (El Midad, 2025)
This study aimed to examine the effect of the traditional games Gobag Sodor and Bentengan on improving the fundamental locomotor movement skills of elementary school students. A quasi-experimental design with a two-group pretest–posttest format was applied to 40 third-grade students at SD Negeri 47 Jambi City. One class participated in Gobag Sodor and the other in Bentengan over eight structured learning sessions. Data were collected using an adapted Test of Gross Motor Development–2 (TGMD-2) instrument and analyzed through paired and independent-sample t-tests with a significance level of 0.05. The results revealed significant improvements in both groups, with Gobag Sodor producing a greater effect (mean difference = 16.15; p < 0.001) than Bentengan (mean difference = 12.20; p < 0.001). The comparative test confirmed that Gobag Sodor was more effective (p = 0.032), supported by a strong effect size (Cohen’s d = 1.5). These findings demonstrate that integrating traditional games into physical education enhances students’ motor competence, motivation, and social interaction while preserving cultural heritage.